Hepatitis C virus infection spontaneous clearance: Has it been underestimated? - Houssein H. Ayoub; Hiam Chemaitelly; Ryosuke Omori; Laith J. Abu-Raddad (International Journal of Infectious Diseases, 2018)
Objectives: Hepatitis C virus (HCV) clearance rate (fclearance) is defined as the proportion of infected persons who will spontaneously clear their infection after acute infection. We aimed to estimate fclearance using a novel approach that avoids limitations in existing estimates, and to clarify the link between fclearance and HCV viremic rate—the latter being the proportion of RNA positivity among those antibody positive. Methods: A mathematical model was developed to describe HCV transmission. fclearance was estimated by fitting the model to probability-based and nationally representative population-based data for Egypt (Egypt 2008 and Egypt 2015) and USA (NHANES A and NHANES B). Uncertainty and sensitivity analyses were conducted. Results: fclearance was estimated at 39.9% (95% uncertainty interval (UI): 34.3%–46.4%) and 33.5% (95% UI: 29.2%–38.3%) for Egypt 2008 and Egypt 2015 data, respectively; and at 29.6% (23.0%–37.1%) and 39.9% (31.2%–51.0%) for NHANES A and NHANES B data, respectively. fclearance was found related to HCV viremic rate through (approximately) the formula fclearance = 1.16 (1 − HCV viremic rate). HCV viremic rate was higher with higher risk of HCV exposure. Robustness of results was demonstrated in uncertainty and sensitivity analyses. Conclusion: One-third of HCV-infected persons clear their infection spontaneously, higher than earlier estimates—the immune-system capacity to clear HCV infection may have been underestimated. Keywords: Clearance rate, Viremic rate, Mathematical model, Infectious disease transmission, Epidemiology